Modulation of triglyceride and cholesterol ester synthesis impairs assembly of infectious hepatitis C virus - Liefhebber, Jolanda M P; Hague, Charlotte V; Zhang, Qifeng; Wakelam, Michael J O; McLauchlan, John (The Journal of biological chemistry, 2014)
In hepatitis C virus infection, replication of the viral genome and virion assembly are linked to cellular metabolic processes. In particular, lipid droplets, which store principally triacylglycerides (TAGs) and cholesterol esters (CEs), have been implicated in production of infectious virus. Here, we examine the effect on productive infection of triacsin C and YIC-C8-434, which inhibit synthesis of TAGs and CEs by targeting long-chain acyl-CoA synthetase and acyl-CoA:cholesterol acyltransferase, respectively. Our results present high resolution data on the acylglycerol and cholesterol ester species that were affected by the compounds. Moreover, triacsin C, which blocks both triglyceride and cholesterol ester synthesis, cleared most of the lipid droplets in cells. By contrast, YIC-C8-434, which only abrogates production of cholesterol esters, induced an increase in size of droplets. Although both compounds slightly reduced viral RNA synthesis, they significantly impaired assembly of infectious virions in infected cells. In the case of triacsin C, reduced stability of the viral core protein, which forms the virion nucleocapsid and is targeted to the surface of lipid droplets, correlated with lower virion assembly. In addition, the virus particles that were released from cells had reduced specific infectivity. YIC-C8-434 did not alter the association of core with lipid droplets but appeared to decrease production of infectious virus particles, suggesting a block in virion assembly. Thus, the compounds have antiviral properties, indicating that targeting synthesis of lipids stored in lipid droplets might be an option for therapeutic intervention in treating chronic hepatitis C virus infection.